Passive shape memory metamaterial and preparation method thereof
Patent Information
- Application Number
- CN202311343198.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-10-13
AI Technical Summary
[0005]针对现有技术的缺陷,本发明的目的在于提供一种无源形状记忆吸波超材料及其制备方法,以解决现有技术无源形状记忆吸波超材料电磁吸收频率窄、难以满足轻量化需求等的技术问题
[0023](1)本发明提供的一种无源形状记忆吸波超材料,包括基板、印制在所述基板上的电磁超材料构件,所述电磁超材料构件具有负泊松比结构,所述负泊松比结构为内凹六边形蜂窝负泊松比结构,所述内凹六边形蜂窝负泊松比结构内为空腔设置;本发明电磁超材料构件选取内凹蜂窝负泊松比结构,具有负泊松比效应,提高了吸波超材料构件的抗冲击能力。本发明无需外加电源、结构简单、控制方便,可在微波频段实现宽带吸收。且空腔结构设置使得本发明吸波超材料满足了轻量化需求。
Smart Images

Figure CN117285808B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic metamaterials technology, and more specifically, relates to a passive shape memory absorbing metamaterial and its preparation method. Background Technology
[0002] With the development of the electronic information age, electromagnetic devices have been widely used in fields such as communications, medicine, electrical engineering, and national defense, which has also increased the demand for designing new electromagnetic materials. Among them, electromagnetic metamaterials, as novel artificial composite structures or composite materials with extraordinary physical properties, have broken through the limitations of traditional natural materials. Relying on artificially formed special media, they possess special electromagnetic transmission properties and can control the basic physical characteristics of electromagnetic waves, such as frequency, amplitude, and phase.
[0003] Electromagnetic metamaterials possess extraordinary electromagnetic properties due to their artificially designed topological structures; therefore, the fabrication process has always been one of the bottlenecks restricting their practical applications. Currently, the main fabrication methods for electromagnetic metamaterials include printed circuit board etching, planar photolithography, and mechanical assembly, which are relatively complex processes and make it difficult to achieve low-cost, rapid, and efficient fabrication of functional electromagnetic metamaterial components with intelligent responses.
[0004] Currently, electromagnetic functional components can be fabricated using fused deposition modeling (FDM) technology, combining shape memory and electromagnetic absorption. This allows for controllable deformation of shape memory polymer composites in response to temperature stimuli, achieving intelligent and controllable broadband electromagnetic absorption. However, existing passive shape memory absorbing metamaterials have narrow electromagnetic absorption bandwidths and are mostly dense solid plates or quasi-plate structures, making it difficult to meet lightweight requirements. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a passive shape memory absorbing metamaterial and its preparation method, thereby solving the technical problems of existing passive shape memory absorbing metamaterials having narrow electromagnetic absorption frequencies and difficulty in meeting lightweight requirements.
[0006] To achieve the above objectives, the present invention provides a passive shape memory absorbing metamaterial, comprising a substrate and an electromagnetic metamaterial component printed on the substrate. The electromagnetic metamaterial component has a negative Poisson's ratio structure, which is a concave hexagonal honeycomb negative Poisson's ratio structure with cavities inside. The electromagnetic metamaterial component is made of a composite material of carbon black, polylactic acid, and polyurethane.
[0007] Preferably, the concave hexagonal honeycomb negative Poisson's ratio structure is a three-dimensional concave honeycomb structure composed of an array of cell units stretched axially.
[0008] Preferably, the length of the concave hexagonal honeycomb of the cell unit is defined as L1, the length of the concave side of the concave hexagon is L2, the thickness of the concave hexagon is t2, the length of the concave hexagonal connecting rod is L3, the thickness of the concave hexagonal connecting rod is t1, and the angle between the length of the concave side of the concave hexagon and the length of the concave hexagonal honeycomb is α; wherein:
[0009] L1 = 8-12 mm, L2 = 4-6 mm, L3 = 4-6 mm, t1 = 0.8-1.2 mm, t2 = 0.4-0.6 mm, α = 60°-75°, and satisfying L1:L2:L3 = 2:1:1, t1:t2 = 2:1.
[0010] Preferably, the mass ratio of carbon black, polylactic acid and polyurethane is (10-20):(64-72):(16-18).
[0011] Preferably, the concave hexagonal honeycomb negative Poisson's ratio structure is axially stretched perpendicular to the substrate, and the stretching length is 20-30 mm.
[0012] Preferably, the substrate is a copper substrate with a thickness of less than or equal to 0.05 mm.
[0013] According to another aspect of the present invention, a method for preparing the aforementioned microwave absorbing metamaterial is provided, which is prepared by 3D printing technology.
[0014] Preferably, the microwave absorbing material is prepared using 3D printing technology, comprising the following steps:
[0015] (1) Carbon black, polylactic acid and polyurethane are mixed in proportion and then pre-baked. Then, the mixture is ball-milled to obtain a mixed raw material. The mixed raw material is melt-blended and extruded to obtain a shape memory composite material.
[0016] (2) Construct the part model of the passive shape memory absorbing metamaterial and perform slicing;
[0017] (3) Using the shape memory composite material obtained in step (1) as the filament, FDM technology is used to print layer by layer on the substrate to obtain the shaped component of the microwave absorbing metamaterial.
[0018] Preferably, the preparation method further includes the step of:
[0019] (4) Drive training is performed on the forming component described in step (3) so that it can achieve shape change under temperature stimulation.
[0020] Preferably, step (4) specifically involves placing the formed component of the microwave absorbing metamaterial described in step (3) in water at 57°C to 60°C to deform the material, and then cooling and shaping it at room temperature; then placing the material in water at 60°C to 70°C to restore its shape, thereby performing drive training.
[0021] In summary, compared with the prior art, the above-described technical solutions conceived by this invention have the following advantages:
[0022] Beneficial effects:
[0023] (1) This invention provides a passive shape memory absorbing metamaterial, comprising a substrate and an electromagnetic metamaterial component printed on the substrate. The electromagnetic metamaterial component has a negative Poisson's ratio structure, which is a concave hexagonal honeycomb negative Poisson's ratio structure with a cavity inside. The concave honeycomb negative Poisson's ratio structure of the electromagnetic metamaterial component of this invention exhibits a negative Poisson's ratio effect, improving the impact resistance of the absorbing metamaterial component. This invention requires no external power supply, has a simple structure, is easy to control, and can achieve broadband absorption in the microwave frequency band. Furthermore, the cavity structure allows the absorbing metamaterial of this invention to meet the requirements of lightweight design.
[0024] (2) The present invention provides a passive shape memory absorbing metamaterial component that can undergo controllable shape changes under temperature stimulation and affect the absorption rate of electromagnetic waves; at the same time, the absorbing metamaterial component has excellent absorption performance in the range of 6GHz-18GHz, with an absorption rate of over 90% and a wide operating band.
[0025] (3) The electromagnetic metamaterial component of the present invention is made of shape memory material, which can realize dynamic adjustment of the absorbing material and change shape under external temperature control.
[0026] (4) This invention provides a method for preparing passive shape memory absorbing metamaterial components. This method uses FDM for preparation, which can effectively reduce material loss, reduce production costs and shorten the production cycle. Attached Figure Description
[0027] Figure 1 A schematic diagram of differential scanning calorimetry curves of a shape memory composite material in one embodiment of the present invention is shown.
[0028] Figure 2 A three-dimensional schematic diagram of a shape memory absorbing metamaterial according to one embodiment of the present invention is shown.
[0029] Figure 3 A schematic diagram of a single-cell planar shape memory absorbing metamaterial according to one embodiment of the present invention is shown.
[0030] Figure 4A schematic diagram of the electromagnetic reflection loss curves of shape memory absorbing metamaterials with different structural parameters t1 in embodiments of the present invention is shown.
[0031] Figure 5 The diagram shows the electromagnetic reflection loss curves of shape memory absorbing metamaterials with different structural parameters L1 in embodiments of the present invention.
[0032] Figure 6 A schematic diagram of a single cell in the hexagonal honeycomb structure of Comparative Example 1 of the present invention is shown.
[0033] Figure 7 The diagram shows electromagnetic reflection loss curves for two structures in Embodiment 1 and Comparative Example 1 of the present invention. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0035] This invention provides a passive shape memory absorbing metamaterial, comprising a substrate and an electromagnetic metamaterial component printed on the substrate. The electromagnetic metamaterial component has a negative Poisson's ratio structure, which is a concave hexagonal honeycomb negative Poisson's ratio structure with cavities inside. The electromagnetic metamaterial component is made of a composite material of carbon black, polylactic acid, and polyurethane.
[0036] In some embodiments, the concave hexagonal honeycomb negative Poisson's ratio structure is a three-dimensional concave honeycomb structure formed by axially stretching an array of cell units. The length of the concave hexagonal honeycomb of the cell unit is defined as L1, the length of the concave side of the concave hexagon as L2, the thickness of the concave hexagon as t2, the length of the connecting rod of the concave hexagon as L3, the thickness of the connecting rod of the concave hexagon as t1, and the angle between the length of the concave side and the length of the concave hexagonal honeycomb as α; wherein:
[0037] L1 = 8-12 mm, L2 = 4-6 mm, L3 = 4-6 mm, t1 = 0.8-1.2 mm, t2 = 0.4-0.6 mm, α = 60°-75°, and satisfying L1:L2:L3 = 2:1:1, t1:t2 = 2:1.
[0038] In some embodiments, the mass ratio of carbon black (CB), polylactic acid (PLA), and polyurethane (TPU) is (10–20):(64–72):(16–18). In preferred embodiments, the weight ratio of PLA to TPU is (3.8–4.2):1, and the weight ratio of CB to the total PLA / TPU is 10:90, 15:85, or 20:80.
[0039] In some embodiments, the concave hexagonal honeycomb negative Poisson's ratio structure is axially stretched perpendicular to the substrate, with a stretching length of 20–30 mm. The substrate is a copper substrate with a thickness of 0.05 mm or less.
[0040] In some embodiments, the microwave absorbing metamaterial is prepared using 3D printing technology.
[0041] In some embodiments, the microwave absorbing structure is fabricated using 3D printing technology, including the following steps:
[0042] (1) Carbon black, polylactic acid and polyurethane are mixed in proportion and then pre-baked. Then, the mixture is ball-milled to obtain a mixed raw material. The mixed raw material is melt-blended and extruded to obtain a shape memory composite material.
[0043] (2) Construct the part model of the passive shape memory absorbing metamaterial and perform slicing;
[0044] (3) The shape memory composite material obtained in step (1) is used as the filament and printed layer by layer on the substrate using FDM technology to obtain the shaped component.
[0045] In some embodiments, the preparation of the microwave absorbing metamaterial further includes the step of:
[0046] (4) The forming component described in step (3) is driven to undergo training so that it can change shape under temperature stimulation. In some embodiments, step (4) specifically involves: placing the passive shape memory absorbing metamaterial described in step (3) in water at 57°C to 60°C, applying deformation to the material, and then cooling and shaping it at room temperature; then placing the material in water at 60°C to 70°C to allow its shape to recover, thereby performing driving training.
[0047] In some embodiments, the pre-drying temperature in step (1) is 60-70℃, and the pre-drying time is 6-10 hours; the ball milling speed is 500-700 r / min, and the ball milling time is 1.5-3 h. The average particle size range of the mixed raw materials after ball milling is 20-50 μm.
[0048] In some embodiments, step (1) involves using a single-screw extruder to melt and blend the mixed raw materials before extrusion. The preheating temperature of the single-screw extruder is 200-220℃, the preheating time is 0.3-0.7h, the extruder head temperature is 160-200℃, the extrusion speed is 90-110r / min, and the diameter of the shape memory composite material filament extruded by the extruder is 2.5-3mm. Step (3) uses FDM technology, with the following specific process parameters: nozzle diameter 0.3-0.5mm, nozzle temperature 200-220℃, printing layer height 0.05-0.15mm, nozzle speed 30-40mm / s, and printing substrate temperature 55-65℃.
[0049] In the following embodiments of the present invention, the carbon black (CB) used is conductive carbon black (7440-44-0); the polylactic acid (PLA) is 4032D (NatureWorks LLC, US); and the polyurethane (TPU) is 6386A (Bayer Company).
[0050] Example 1
[0051] The method for preparing the composite material in this embodiment specifically includes the following steps:
[0052] Step 1: Take the weight ratio of CB:PLA:TPU as 20:64:16, weigh it according to the ratio, and put it into a 60℃ oven for pre-drying for 8 hours.
[0053] Step 2: The pre-baked PLA, TPU, and CB were mixed using a three-dimensional mechanical mixer at a mixing speed of 600 r / min for 2 hours. The final average particle size of the mixed PLA, TPU, and CB powder was 35 μm.
[0054] Step 3: Add the uniformly mixed powder to the feed inlet of a single-screw extruder, preheat for 0.5 hours at 210℃, set the extruder head temperature to 180℃, and the extrusion speed to 100 r / min. After melting and blending the raw materials, extrude to obtain shape memory composite filaments with a diameter of 2.85±0.1 mm. Figure 1 This is a schematic diagram of the differential scanning calorimetry curve of the shape memory composite material, which calibrates the glass transition temperature to be approximately 56.6℃.
[0055] Step 4: Use the 3D modeling software Solidworks 2018 to draw the model. Figure 3The concave hexagonal honeycomb structure shown is defined as follows: the length of the concave hexagonal honeycomb of the cell unit is L1, the length of the concave side of the concave hexagon is L2, the thickness of the concave hexagon is t2, the length of the connecting rod of the concave hexagon is L3, the thickness of the connecting rod of the concave hexagon is t1, and the angle between the length of the concave side and the length of the concave hexagonal honeycomb is α; where L1 = 10mm, L2 = 5mm, L3 = 5mm, t1 = 1mm, t2 = 0.5mm, α = 60°, and the planar figure is stretched by 30mm to form a three-dimensional structure.
[0056] by Figure 2 Taking the schematic diagram of the three-dimensional electromagnetic metamaterial as an example, the array is arranged along the x and y directions to 12:22, and finally an electromagnetic metastructure of 180×190×30mm is formed. A cuboid of 180×190×0.05mm is drawn at the bottom of the three-dimensional lattice structure, forming a complete three-dimensional wave-absorbing metamaterial component.
[0057] The three-dimensional absorbing metamaterial was sliced using three-dimensional slicing software, and the resulting STL file of the layered slices was output and the information was input into the control software of the FDM device.
[0058] The FDM process uses the single shape memory polymer composite filament obtained in the above steps as raw material. The FDM printing parameters include a nozzle diameter of 0.4 mm, a nozzle temperature of 210°C, a printing layer height of 0.1 mm, a nozzle speed of 35 mm / s, and a printing substrate temperature of 60°C.
[0059] The FDM process is used to print layer by layer. After each facet is manufactured, the worktable is lowered by one layer thickness. The FDM forming part is lowered by 0.1mm for each layer. This process is repeated to print the next layer. This cycle is repeated to complete the manufacturing of each layer structure.
[0060] After printing, the absorbing structure is allowed to cool naturally on the substrate, and then the component is removed from the printing substrate using a spatula, ultimately obtaining a passive shape memory absorbing metamaterial.
[0061] The driving training of the shaped part is specifically carried out by placing the shaped shape memory electromagnetic metamaterial in water at 58°C, applying deformation to the shaped part, and then cooling and solidifying it at room temperature; then placing the shaped part in water at 65°C to allow the shape memory electromagnetic metamaterial part to recover, thereby carrying out driving training.
[0062] Figure 4 A schematic diagram of the electromagnetic reflection loss curve of the three-dimensional electromagnetic absorbing metamaterial in Example 1 is shown (curve 1 indicates t1 = 1 mm). Figure 4As shown, the three-dimensional electromagnetic wave-absorbing metamaterial has a reflection loss of less than -10dB at a frequency of 6-18GHz, that is, an absorption rate of more than 90%, and an absorption peak of -39.73dB.
[0063] Example 2
[0064] The rest is the same as in Example 1, except that in step one, the weight ratio of CB:PLA:TPU in the weighing and pre-drying is 15:68:17. After weighing according to the ratio, it is placed in a 60℃ oven for pre-drying for 8 hours.
[0065] Example 3
[0066] The rest is the same as in Example 1, except that in step one, the weight ratio of CB:PLA:TPU in the weighing and pre-drying is 10:72:18. After weighing according to the ratio, it is placed in a 60℃ oven for pre-drying for 8 hours.
[0067] The glass transition temperatures of the shape memory composite filaments obtained in Examples 2 and 3 are 57.1°C and 57.5°C, respectively. The shape memory electromagnetic metamaterials formed from these materials can be placed in water at 58°C to deform the formed part, and then cooled and solidified at room temperature. The formed part is then placed in water at 65°C to allow the shape memory electromagnetic metamaterial part to recover, thereby enabling drive training.
[0068] Example 4
[0069] The rest is the same as in Example 1, except that in step four, the drawing is created using the 3D drawing software Solidworks 2018. The parameters are: L1 = 10mm, L2 = 5mm, L3 = 5mm, t1 = 0.8mm, t2 = 0.4mm, α = 60°, and the planar graphic is stretched by 30mm to form a 3D structure.
[0070] Figure 4 A schematic diagram of the electromagnetic reflection loss curve of the three-dimensional electromagnetic absorbing metamaterial in Embodiment 4 is shown (curve 1 represents the thickness t1 of the concave hexagonal connecting rod when it is 1 mm, and curve 0.8 represents the thickness t1 of the concave hexagonal connecting rod when it is 0.8 mm). Figure 4 As shown, the three-dimensional electromagnetic wave-absorbing metamaterial exhibits a reflection loss of less than -10dB at frequencies of 6.8-18GHz, meaning its absorption rate is greater than 90%. Compared to Example 1, when the thickness of the connecting rod decreases, the absorption peak value may decrease and the bandwidth may slightly narrow due to increased porosity, but broadband absorption is still maintained.
[0071] Example 5
[0072] The rest is the same as in Example 1, except that in step four, the drawing is created using the 3D drawing software Solidworks 2018. The parameters are: L1 = 8mm, L2 = 4mm, L3 = 4mm, t1 = 1mm, t2 = 0.5mm, α = 60°, and the planar graphic is stretched by 30mm to form a 3D structure.
[0073] Example 6
[0074] The rest is the same as in Example 1, except that in step four, the drawing is created using the 3D drawing software Solidworks 2018. The values are: L1 = 12mm, L2 = 6mm, L3 = 6mm, t1 = 1mm, t2 = 0.5mm, α = 60°, and the planar graphic is stretched by 30mm to form a 3D structure.
[0075] Figure 5 A schematic diagram of the electromagnetic reflection loss curves of the three-dimensional electromagnetic absorbing metamaterials in Examples 1, 5, and 6 is shown (curves 8, 12, and 10 represent the absorbing metamaterials corresponding to L1 values of 8 mm, 12 mm, and 10 mm in Examples 1, 5, and 6, respectively). Figure 5 As shown, the three-dimensional electromagnetic absorbing metamaterial exhibits a reflection loss of less than -10dB in the frequency range of 8-18GHz, indicating an absorption rate greater than 90%. Compared to Example 1, Examples 5 and 6 show narrower bandwidths. The change in the size of L1 causes an overall shift in the reflection loss curve; the curve shifts towards lower frequencies as the size decreases, and vice versa. The overall reduction in size increases the absorption peak value in Example 5, while decreasing it in Example 6.
[0076] Comparative Example 1
[0077] The conditions are the same as in Example 1, except that in step four, the 3D drawing software Solidworks 2018 is used to draw the image. Figure 6 The hexagonal honeycomb unit cell shown has L = 10 mm, t = 1 mm, and a vertical thickness of 30 mm.
[0078] Figure 7 A schematic diagram of the electromagnetic reflection loss curves of the three-dimensional electromagnetic absorbing metamaterials of this comparative example and Example 1 is shown. Figure 7 As shown, the three-dimensional electromagnetic wave-absorbing metamaterial has a reflection loss of less than -10dB at frequencies of 4.2-5, 6.7-8, and 9-18GHz, i.e., an absorption rate of greater than 90%, and an absorption peak of -33.92dB. It can be seen that the overall bandwidth and peak value of the regular hexagonal honeycomb structure in Comparative Example 1 are significantly reduced compared to the concave hexagonal honeycomb wave-absorbing metamaterial in Example 1, and the performance is obviously degraded.
[0079] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A passive shape memory absorbing metamaterial, characterized in that, The invention includes a substrate and an electromagnetic metamaterial component printed on the substrate. The electromagnetic metamaterial component has a negative Poisson's ratio structure, which is a concave hexagonal honeycomb negative Poisson's ratio structure, and the concave hexagonal honeycomb negative Poisson's ratio structure has a cavity inside. The concave hexagonal honeycomb negative Poisson's ratio structure is a three-dimensional concave honeycomb structure composed of an array of cell units stretched axially. The length of the concave hexagonal honeycomb of each cell unit is defined as L1, the length of the concave side of the concave hexagon as L2, the thickness of the concave hexagon as t2, the length of the connecting rod of the concave hexagon as L3, the thickness of the connecting rod of the concave hexagon as t1, and the angle between the length of the concave side of the concave hexagon and the length of the concave hexagonal honeycomb as α. Wherein: L1 = 8~12 mm, L2 = 4~6 mm, L3 = 4~6 mm, t1 = 0.8~1.2 mm, t2 = 0.4~0.6 mm, α = 60°~75°, and satisfying L1: L2: L3 = 2:1:1, t1: t2 = 2:1; The electromagnetic metamaterial component is made of a composite material of carbon black, polylactic acid and polyurethane; the mass ratio of carbon black, polylactic acid and polyurethane is (10-20):(64-72):(16-18).
2. The microwave absorbing metamaterial as described in claim 1, characterized in that, The concave hexagonal honeycomb negative Poisson's ratio structure is stretched axially perpendicular to the substrate, with a stretching length of 20-30 mm.
3. The microwave absorbing metamaterial as described in claim 1, characterized in that, The substrate is a copper substrate with a thickness of less than or equal to 0.05 mm.
4. The method for preparing the microwave absorbing metamaterial according to any one of claims 1 to 3, characterized in that, It was prepared using 3D printing technology.
5. The preparation method according to claim 4, characterized in that, The microwave absorbing metamaterial is prepared using 3D printing technology, comprising the following steps: (1) Carbon black, polylactic acid and polyurethane are mixed in proportion and pre-dried, then ball-milled to obtain mixed raw materials. The mixed raw materials are melt-blended and extruded to obtain shape memory composite materials. (2) Construct a part model of the passive shape memory absorbing metamaterial and perform slicing processing; (3) Using the shape memory composite material obtained in step (1) as the filament, FDM technology is used to print layer by layer on the substrate to obtain the shaped component of the microwave absorbing metamaterial.
6. The preparation method according to claim 5, characterized in that, It also includes the following steps: (4) Drive training is performed on the forming component described in step (3) so that it can achieve shape change under temperature stimulation.
7. The preparation method according to claim 6, characterized in that, Step (4) specifically involves placing the formed component of the microwave absorbing metamaterial described in step (3) in water at 57°C to 60°C to deform the material, and then cooling and shaping it at room temperature; then placing the material in water at 60°C to 70°C to restore its shape, thereby performing drive training.
Citation Information
Patent Citations
Shape memory metamaterial and preparation method thereof
CN102480014A
Method for manufacturing biodegradable shape-memory polymer intravascular stent additive with negative poisson ratio
CN106236338A